Maintenance Propeller Hartzell Pada Pesawat Cessna 172 - Maidi Saputra; Ibnu Hakim (universitas teuku umar, 2018)
Cessna 172 aircraft type is the type of aircraft being used as a learning tool for novice aviators who has how many components it needs to do maintenance and repair, such as propeller (propeller). This is done so that the plane was in decent condition wear or fly. It is therefore necessary to make a repair or maintenance procedure the components of the aircraft Cessna 172 and the settlement of the problems found during the treatment and repair the aircraft. Examination of the propeller generally has a certain interval, for example 25; 50; or 100 hours, including Blade, spinner and other applications, which aims to see the excess oil; section blade and hub to investigate blade damage, spinner and hub to check for scratches or other defects. And completion trouble shooting, including excessive friction, increase in RPM or torque, oil leaks and lubricants, and excess motion. Keywords: airplane, a Cessna 172, propeller, Troubleshooting